A Narrowing Diagnosis: A Rare Cause of Adult Croup and Literature Review. (10th January 2017) - Patel, Jayshil J.; Kitchin, Emily; Pfeifer, Kurt
Abstract : Croup or laryngotracheitis is rare in adults. We present a case of an otherwise healthy young woman that presented in the winter with 3 days of increasing dyspnea, cough, and fever. She was hemodynamically stable but was found to have a barking cough, paradoxical abdominal breathing, and stridor. Chest radiograph revealed subglottic narrowing. Respiratory viral nucleic acid amplification testing was positive for respiratory syncytial virus. The patient was treated with nebulized epinephrine, dexamethasone, and a helium-oxygen mixture. Stridor resolved immediately after starting the helium-oxygen mixture. Within 72 hours, the patient made a complete clinical recovery without the need for escalation of care. Prehospital discharge chest radiograph demonstrated resolution of subglottic narrowing.